PLURALISM: "PROGRESSIVE MUSLIMS" ADDRESSING RADICALISM (A Philosophical-Hermeneutical Approach in Islamic Studies) - Joseph Ell (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Faith in Islam is considered a divine blessing for all Muslim communities. As a divine mercy, faith is intricately linked to humanity, influencing moral character and virtues. However, radicalism, understood as the fundamentalist ideology and extremist movements of certain Islamic groups, rejects coexistence in diversity and refuses pluralism. This exclusive spirit not only harms interfaith harmony but also poses internal challenges within the Muslim community. Progressive Muslims, as a more open and flexible trend and movement, advocate for the values of Pluralism as essential aspects of humanity and religiosity. This is manifested in inter-subjective and inter-faith relations, as well as in the spirit of sharing love and compassion. The author employs a philosophical-hermeneutical method to qualitatively understand and interpret the central components of this writing, namely radicalism, the concept of pluralism in the context of Progressive Muslims popularized by Omid Safi, and the Multiple Critique Method.